A case study of the information technology applications of the major service libraries of the armed forces of the Philippines - Siena, Dandeelo S. (School of Library and Information Studies, University of the Philippines Diliman, 1999)
This study describes how the major service libraries of the Armed Forces of the Philippines are adapting to the current trends in information technology. It determines the administrative organization, library materials available and the information technology applications currently in use in these libraries, and recognizes the strengths and weaknesses of the libraries' resources and services.